Clinical utility of Epstein‐Barr virus DNA and other liquid biopsy markers in nasopharyngeal carcinoma. Issue 11 (28th September 2020) - Tan, Rong; Phua, Sean Kean Ann; Soong, Yoke Lim; Oon, Lynette Lin Ean; Chan, Kian Sing; Lucky, Sasidharan Swarnalatha; Mong, Jamie; Tan, Min Han; Lim, Chwee Ming
Abstract: Nasopharyngeal carcinoma (NPC) is a malignant epithelial tumor ubiquitously associated with the Epstein‐Barr virus (EBV), which is highly prevalent in South China, Southeast Asia, and North Africa. Despite being a highly radio‐sensitive and treatable cancer, a majority of NPC patients are diagnosed in their advanced stage, and locoregional and distant relapses following definitive treatment contribute largely to cancer‐specific mortality among these patients. Given that EBV‐driven NPC is the predominant variant seen in endemic regions, various EBV detection methods have been developed and are utilized in screening, prognostication, and post‐treatment surveillance of NPC patients. While the Immunoglobulin A (IgA) serology assay is the most extensively studied EBV detection method, the detection of plasma EBV DNA released during replication or cellular apoptosis has shown superior outcomes in endemic population screening, prognostication, and detection of distant relapse. Furthermore, there is emerging evidence on the use of circulating tumor cells, microRNAs, DNA hypermethylation, and combination assays in various clinical scenarios. Herein, this paper provides a comprehensive overview of the relevant studies using various EBV detection techniques in the management of NPC. Specifically, the recent advances, clinical evidence, and challenges associated with the clinical application of EBV liquid biopsies in population screening, prognostication, and surveillance of NPC are presented.